2019
DOI: 10.1016/j.chiabu.2019.104094
|View full text |Cite
|
Sign up to set email alerts
|

Childhood adversity and psychosis in detained inpatients from medium to high secured units: Results from the Scottish census survey

Abstract: Background: There is limited data available regarding the most common forms of psychiatric illness, the occurrence of childhood adversity, and the link between childhood adversity and criminal and psychiatric outcomes amongst forensic inpatients. Aims: Using census data for all Scottish forensic inpatients, we investigated the most common primary psychiatric diagnoses in forensic settings, the occurrence of childhood adversity amongst forensic inpatients, and whether childhood adversity experiences significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 33 publications
2
9
1
Order By: Relevance
“…The prevalence rates were comparable to those reported in the literature for adults with intellectual disabilities in secure services (Morris et al , 2019), although higher than those reported by O'Brien et al (2010) who report that 35% had experienced ACEs prior to admission. Prevalence rates were also higher than those reported previously in adolescent and adult prison (Ford et al , 2019) and forensic populations (Karatzias et al , 2019). Furthermore, the total number of ACEs for males in the study was comparable to the number of ACEs reported in a study in the Democratic Republic of the Congo (DRC) with adolescents (Mels et al , 2009), albeit without the comparative social, political and economic context of the DRC.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…The prevalence rates were comparable to those reported in the literature for adults with intellectual disabilities in secure services (Morris et al , 2019), although higher than those reported by O'Brien et al (2010) who report that 35% had experienced ACEs prior to admission. Prevalence rates were also higher than those reported previously in adolescent and adult prison (Ford et al , 2019) and forensic populations (Karatzias et al , 2019). Furthermore, the total number of ACEs for males in the study was comparable to the number of ACEs reported in a study in the Democratic Republic of the Congo (DRC) with adolescents (Mels et al , 2009), albeit without the comparative social, political and economic context of the DRC.…”
Section: Discussioncontrasting
confidence: 60%
“…By contrast, large-scale US and UK studies consistently report prevalence rates of around 50% for exposure to one or more ACEs in neurotypical populations (Campbell et al , 2016; Ford et al , 2016). Further inflated rates of 80–90% have been reported for forensic (Karatzias et al , 2019) and prison populations (Ford et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…44 We suggest that something akin to the ‘Scottish effect’, specifically in terms of biopsychosocial stress and the resultant physiological stress response, is being observed among mainstream and forensic psychiatric populations. High levels of adverse life events observed among Scottish forensic patients 45 together with the dose–response association observed between adverse life events/psychological distress and a negative impact upon subjective and objective physical health 46 may be evidenced within our reported cohort. There is increasing physiological evidence of heightened levels of oxidative stress and inflammation within anxiety, depressive, bipolar disorder and schizophrenia.…”
Section: Discussionsupporting
confidence: 57%
“…High rates of various types of child victimization are reported also in forensic mental health patients, with maltreatment reported for 75-85% (19)(20)(21)(22)(23). A handful of studies have addressed the pertinent question of associations between child victimization and violent and criminal behavior in forensic patients.…”
Section: Introductionmentioning
confidence: 99%